The relationships between gas production and chemical composition of 23 browses of the genus Sesbania - Nsahlai, I.V.; Siaw, D.E.K.A.; Osuji, P.O. (Wiley, 1994)
This study evaluates the differences in the gas produced by Sesbania accessions and related gas production to macro-constituents and tannin content of the browse species. Fresh samples were incubated in triplicate in a medium prepared from sieved rumen liquor harvested from two rumen-fistulated cows fed native pasture hay ad libitum and 2.0 kg cottonseed cake per head per day. Sesbania species had similar rates of gas production but differed in the volume of gas produced. The ranking order for gas production was S. grandiflora > S. sesban > S. keniensis > S. goetzei. There was little variation in the gas production parameters within S. grandiflora and S goetzei. But the variation was larger within S. sesban. Regression analysis showed that the rate of gas production was negatively affected by the lignin content of the browses, but the volume of gas produced was negatively related to the neutral detergent fibre, hemicellulose, lignin and insoluble proanthocyanidins content of browses. Cluster analysis showed a broad agreement between gas production constants, macro-constituents and tannin contents in classifying accessions into high or low nutritive value groups.